Chinese loanwords in the OED - de la Cruz Cabanillas, Isabel (Adam Mickiewicz University, 2008)
It was traditionally assumed that Chinese had contributed few borrowings into English until Cannon (1987, 1988, 1990) carried out his research based on different English desk-dictionaries. His studies were supplemented by Moody (1996) who reviewed Cannon’s list focusing on the information provided by the Oxford English dictionary (henceforth OED) and Webster’s third new international dictionary of the English language. Nonetheless, Moody’s analysis did not explore all the possibilities the OED offered at the time. This articles aims at revising those previous pieces of work on the topic to find out whether there are significant changes in view of the latest data supplied by the OED, to determine whether there is an increase in the number of items borrowed, which are the transmission and source languages and to see whether any predictions for the near future can be made. Finally, some comments on the transliteration of the terms are also included.